Effects of Dill (Anethum graveolens) Essential Oil and Lipid Extracts as Novel Antioxidants and Antimicrobial Agents on the Quality of Beef Burger - Milo Mujović; Branislav Šojić; Tatjana Peulić; Sunčica Kocić-Tanackov; Predrag Ikonić; Danica Božović; Nemanja Teslić; Miloš Županjac; Saša Novaković; Marija Jokanović; Snežana Škaljac; Branimir Pavlić (Foods, 2024)
Dill (Anethum graveolens L.) essential oil (DEO) obtained by hydrodistillation (HD) and lipid extracts (DSE1 and DSE2) obtained by supercritical CO2 extraction (SFE) were used as potential antioxidants and antimicrobial agents in beef burgers at two different concentrations (0.075 and 0.15 µL/g). The chemical profile of the lipid extracts and their in vitro antimicrobial activity against the common pathogens E. coli and L. monocytogenes (MIC and MBC) were determined. The quality and shelf life of the burgers were monitored through (lipid oxidation—TBARS test; protein oxidation—thiol group content and selected biogenic amine content) and microbiological quality (Enterobacteriaceae—EB, aerobic mesophilic bacteria—TAMB, lactic acid bacteria—LAB). Dill lipid extracts (DEO and DSE1) significantly (p < 0.05) reduced lipid oxidation and protein oxidation in beef burgers, while the lipid extract (DSE2) showed pro-oxidative effects. The strongest antimicrobial potential against EB was found in SFE1150 (1.15 log cfu/g). Putrescine, cadaverine, histamine, and tyramine were not detected in any of the analyzed samples during the storage period, while the total content of biogenic amines ranged from 21.4 mg/kg to 285 mg/kg. Generally, it can be concluded that dill essential oil (DEO) and extract DSE1 can be used as novel natural additives in minced-meat products.